Perjumpaan Antara Spiritualisme dan Solidaritas pada Pesta Nelayan di Baurung Kabupaten Majene - Abdul Rahman (LPPM Politeknik Pratama, 2023)
This study aims to determine the background, process, social function and meaning of the Pappassoq Fisherman's Party Traditional Ceremony for the fishermen community in Baurung Village. This study uses interviews, direct observation and documentation. The results showed that the background for the appearance of the pappassoq traditional ceremony was the existence of a mandate from their ancestors for generations, as a form of gratitude for the abundant catch of fish. Pappassoq is held once a year in December, under the lambe tree. Pappassoq's social functions are spiritual functions, social solidarity functions, entertainment functions and economic functions. The meaning of Pappassoq is the meaning of the people's belief in myths and the occult, the meaning in prayer as a form of hope and the meaning of the symbols used in carrying out the ceremony.